2017
DOI: 10.1039/c6pp00337k
|View full text |Cite
|
Sign up to set email alerts
|

Serum endocannabinoids and N-acyl ethanolamines and the influence of simulated solar UVR exposure in humans in vivo

Abstract: Solar ultraviolet radiation (UVR) exposure of human skin has beneficial and harmful effects on health, including impact on immune function, inflammation and reportedly mood, but these are not fully elucidated. Since the endocannabinoid system is implicated in many activities including mood alteration, our objective was to (i) determine and quantify circulating levels of a wide range of endocannabinoid and N-acyl ethanolamine (NAE) species (ii) evaluate whether these are modulated by cutaneous UVR exposures, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Recently, studies in humans in vivo showed that exposure to UVR (5% UVB, 95% UVA) modulated the cutaneous endocannabinoid system [31], while exposure to UVA radiation (315–400 nm) reduced blood pressure [32]. Further studies are required to assess the impact of sun exposure on these and further potential health benefits beyond vitamin D synthesis, while the latter is the current established benefit and hence the focus of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies in humans in vivo showed that exposure to UVR (5% UVB, 95% UVA) modulated the cutaneous endocannabinoid system [31], while exposure to UVA radiation (315–400 nm) reduced blood pressure [32]. Further studies are required to assess the impact of sun exposure on these and further potential health benefits beyond vitamin D synthesis, while the latter is the current established benefit and hence the focus of this work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both 2-AG and AEA are folds-higher in the serum of patients with endotoxic shock than control serum (Wang et al, 2001). Circulating endocannabinoids are increased in patients with cirrhosis (Fernandez-Rodriguez et al, 2004); chronic hepatitis C infection (Patsenker et al, 2015); exposure to solar ultraviolet radiation (Felton et al, 2017); congestive heart failure (Weis et al, 2010b); and atherosclerosis (Maeda et al, 2009). Similarly, rats with acute pancreatitis also exhibit significantly elevated circulating AEA concentrations, particularly in animals with a severe, necrotizing pancreatitis (Matsuda et al, 2005).…”
Section: Circulating Endocannabinoids and Inflammationmentioning
confidence: 99%
“…Bone marrow flush (pool of three mice) was processed in order for the extraction of endocannabinoids and N-acyl ethanolamines. 46,47 Samples were analysed on a triple quadrupole mass spectrometer (Xevo TQ-S, Waters) with electrospray ionisation probe coupled to an ultra-high performance liquid chromatography pump (UPLC, Acquity, Waters) (UPLC-MS/MS; the analytes were quantified via multiple reaction monitoring assays using deuterated internal standards and internal calibration lines. Details concerning extraction and analysis can be found in the Supplementary Methods.…”
Section: Uplc-ms/ms Analysis Of Endocannabinoids and N-acyl Ethanolammentioning
confidence: 99%